AH-25 Sperm Morphology of the Javan Muntjak, Muntiacus muntjak muntjak - Sri Wahyuni; Gholib Gholib; Wahono Esthi Prasetyaningtyas; I Ketut Mudite Adnyane; Srihadi Agungpriyono; Hamny Hamny; Muhammad Jalaluddin; Mustafa Sabri; Muslim Akmal; Muhammad Agil; Tuty Laswardi Yusuf (Media Veteriner, 2015)
Sperm Morphology of the Javan Muntjak, Muntiacus muntjak muntjak